Islam and Secularity - Göle, Nilüfer.
1 online resource (276 pages)
Keywords: In Islam and Secularity Nilüfer Göle examines the transforming relationship between Islam and Western secular modernity and the impact of the Muslim presence in Europe. She demonstrates that Islam and secularism are mutually constitutive, constantly changing, and that the presence of Islam unsettles dominant narratives of Western modernism.